Point of View (POV) Promotion of View and Hearing through Virtual-Based Tourism as a Stimulus for Tourists' Interest in Visiting - Rahayu, Denok Wahyudi Setyo; Septiawan, Bambang; Hamidah, Aqnes Dwi Sakti (PT Inovasi Pratama Internasional, 2024)
Point of view (POV) of virtual-based tourism as the perspective of each individual on virtual-based tourism. Following the era of development, promotional media are very diverse and can be chosen according to needs. One way of promotion is visual promotion through virtual-based tourism in the form of videos that display the conditions of tourist attractions in a visual-auditory display so that viewers can see what is in the tourist attraction. Tourism products are service products that are in great demand by tourists to relieve fatigue from all daily activities. Taman Kebon Rojo Blitar is a tourist attraction that can be an alternative choice for tourism that provides a combination of flora, fauna, and artificial tourism in the form of play areas and culinary delights located around the park. The eye-catching atmosphere of the Taman Kebon Rojo tourist spot is very much needed to make the appearance of the audio-visual video attractive and can be a stimulus for tourists' interest in visiting. The objective of this research is to analyze whether the point of view of the audio-visual promotion through a virtual-based tourist display could provide a stimulus for video viewers to visit the tourist spot directly. The research method used a quantitative method by employing a survey through a questionnaire and showing a video of the Taman Kebon Rojo Blitar tourist spot to respondents. After that, it is calculated by applying multiple linear regression to determine whether the audio-visual promotion in the form of a video could provide a stimulus for tourists' interest in visiting. The results prove that virtual promotion which consists of promotional objectives (X1) and tourism promotional mix (X2) is able to significantly increase tourist interest in visiting (Y) both partially and simultaneously for 58,9%.